Guidance Scheme for Gun-Launched Gliding Guided Projectiles - Kim, Boseok; Shin, Minjae; Lee, Chang-Hun; Kim, Jin-Won; Lee, Young-Ki; Park, Sung-Woo (IEEE transactions on aerospace and electronic systems, 2025)
This article presents a composite guidance approach tailored for gun-launched gliding-guided projectiles. The guidance scheme is designed to maximize the lift-to-drag ratio during the gliding flight phase, thereby extending flight range while adhering to impact angle constraints in the terminal homing phase to enhance warhead effectiveness. Given the inherent variability in initial glide conditions arising from operational characteristics, the proposed guidance strategy is designed to prioritize following optimal velocity rather than optimal glide path angle. For the terminal homing phase, the proposed approach integrates optimal impact angle guidance with an enhanced time-to-go and final velocity prediction method, taking into account aerodynamic drag and gravity effects. To facilitate a seamless transition in guidance, we propose a method for determining an appropriate switching point. Furthermore, we analyze the maximum achievable target range and impact angle within specified maneuvering limits. One of the key features of the proposed method is its formulation as a generalized guidance scheme aimed at maximizing flight range, offering advantages over existing methods. Moreover, despite its simplicity, the proposed approach achieves performance comparable to that of optimization results. Finally, we validate our findings through numerical simulations.